Engineering and Economic Strategies for Manufacturing SMEs in Nigeria: Coping with Wage Inflation and Fuel Price Surge (Case Study) - Wilson, Emmanuel Okon; Amgbari, Charles Onyinegbaliwene (Management Analytics and Social Insights, 2025)
This study investigates the engineering and economic strategies adopted by manufacturing SMEs in Nigeria to cope with the sharp increase in minimum wage from ₦30,000 to ₦70,000 and the significant rise in fuel costs from ₦650 to nearly ₦1,500 per liter (ref with duration of time extremes). Through a comprehensive analysis of the manufacturing sector, the research identifies various operational optimization techniques, such as lean manufacturing, automation, and energy-efficient technologies that have been implemented to counterbalance rising production costs. The study also explores the shift towards alternative energy sources, such as solar power and biodiesel, which have helped firms reduce dependency on expensive fuel. Financial management strategies, including cost-cutting measures, renegotiation of supplier contracts, and adjustments in pricing models, were also evaluated. Labor productivity improvements, achieved through training programs and workforce restructuring, have enabled SMEs to meet the compulsory payment of the new minimum wage without significantly eroding profit margins. The findings highlight the critical role of government interventions, such as tax incentives and grants, in supporting SMEs during this period of economic adjustment. By utilizing a mixed-method approach of surveys, case studies, and economic modelling, this research offers practical insights into how Nigerian manufacturing SMEs have maintained competitiveness and operational sustainability amidst the dual pressures of wage inflation and fuel price surges.